A trajectory‐based classification of ERA‐Interim ice clouds in the region of the North Atlantic storm track. Issue 12 (28th June 2016) - Wernli, Heini; Boettcher, Maxi; Joos, Hanna; Miltenberger, Annette K.; Spichtinger, Peter
Abstract: A two‐type classification of ice clouds (cirrus) is introduced, based on the liquid and ice water content, LWC and IWC, along air parcel backward trajectories from the clouds. In situ cirrus has no LWC along the trajectory segment containing IWC; it forms via nucleation from the gas phase. In contrast, liquid‐origin cirrus has both LWC and IWC along their backward trajectories; it forms via lifting from the lower troposphere and freezing of mixed‐phase clouds. This classification is applied to 12 years of ERA‐Interim ice clouds in the North Atlantic region. Between 400 and 500 hPa more than 50% are liquid‐origin cirrus, whereas this frequency decreases strongly with altitude (<10% at 200 hPa). The relative frequencies of the two categories vary only weakly with season. More than 50% of in situ cirrus occur on top of liquid‐origin cirrus, indicating that they often form in response to the strong lifting accompanying the formation of liquid‐origin cirrus. Key Points: Air parcel trajectories are used to classify ice clouds into in situ and liquid‐origin ice clouds Over the North Atlantic near 300 hPa about one third of all ice clouds are liquid‐origin ice clouds More than 50% of in situ cirrus occur on top of liquid‐origin cirrus indicating a strong dynamical linkage